Association between Frontal-Executive Dysfunction and Speech-in-Noise Perception Deficits in Mild Cognitive Impairment - Lee, Soo Jung (J Clin Neurol, 2018)
BACKGROUND AND PURPOSE: Speech-in-noise perception deficits have been demonstrated in patients with mild cognitive impairment (MCI). However, it remains unclear whether the impairment of speech perception varies between MCI subtypes. The purpose of this study was twofold: 1) to compare speech perception performance among MCI subgroups, and 2) to identify the cognitive domains specifically related to speech-in-noise perception. METHODS: We studied 46 patients with MCI and 39 hearing-threshold-matched cognitively normal elderly (CNE) subjects. Two different patient classifications were used: 1) patients with amnestic mild cognitive impairment (aMCI) (n=21) or nonamnestic mild cognitive impairment (naMCI) (n=25), and 2) patients with frontal-executive dysfunction (FED) (n=16) or without FED (n=30). All of the subjects underwent audiometric, neuropsychological, and speech perception assessments. Speech-in-noise perception was measured using sentence recognition tests in the presence of two types of background noise at four levels. RESULTS: First, as the level of background noise increased, the MCI with FED group scored lower than both the MCI without FED and CNE groups under both types of noise. Second, both the naMCI and aMCI groups scored lower than the CNE group, but there were no differences between the naMCI and aMCI groups in sentence recognition under any noise conditions. Third, significant correlations were found between sentence recognition and executive function scores both in the MCI groups and in the CNE group. CONCLUSIONS: Our findings suggest that frontal-executive function is strongly related to speech-in-noise perception and that MCI patients with FED have greater deficits in speech-in-noise perception compared to other subgroups of MCI.